PAPER CRAFT UNTUK PENGENALAN KOMPONEN KOMPUTER DASAR PADA SANTRI TPQ MIFTAHUL HUDA - Istiqomah, Iis; Irawati, Okta; Noviana, Widyah (JAMAIKA: JURNAL ABDI MASYARAKAT, 2025)
This Community Service Activity aims to improve the basic digital literacy of children at TPQ Miftahul Huda through the paper craft method as an educational medium for basic computer architecture. The activity participants numbered 25 children aged 7–12 years, who were accompanied by 1 TPQ teacher and 3 facilitators from the community service team. The implementation method is carried out in the form of a face-to-face workshop that includes short lectures, demonstrations, paper craft assembly practice, interactive discussions, and simple evaluations. Paper craft media is used to introduce computer components such as CPUs, monitors, keyboards, and mice in a concrete and fun way without using computer devices directly. The results of the activity show an increase in the percentage of children who are able to name at least three basic computer components from 32% before the activity to 84% after the activity. In addition to improving cognitive understanding, this activity also encourages active participation, creativity, and fine motor skills of children during the learning process. Thus, the paper craft method has proven effective as an alternative learning medium to improve children's basic digital literacy in non-formal educational environments with limited facilities, and has the potential for sustainable replication. Keywords: paper craft, basic computer architecture, digital literacy, TPQ, community service